2017
DOI: 10.1111/jop.12623
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of the immunohistochemical detection of cancer‐associated fibroblasts in oral cancer: A systematic review and meta‐analysis

Abstract: AIM:To perform a meta-analysis to assess whether the presence of cancer-associated fibroblasts (CAF) is a prognostic marker of oral squamous cell carcinomas (OSCC). METHODS:Immunohistochemical studies assessing the prognostic relevance of CAF (alpha smooth muscle actin (α-SMA)-positive fibroblasts) in patients with OSCC were systematically reviewed using Cochrane, Lilacs, PubMed, Scopus and Web of Science databases. The outcomes assessed were overall survival (OS) and disease-free survival (DFS). The meta-anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
56
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 66 publications
(61 citation statements)
references
References 40 publications
5
56
0
Order By: Relevance
“…Vascular endothelial growth factor and other growth factors such as epidermal growth factor are derived from stromal cells and endothelial cells, and promote tumour angiogenesis, which enhances tumour growth, survival, and metastasis . In OTSCC, CAFs identified by the use of α‐smooth muscle actin have been reported as key players in tumour progression, and they serve as an important prognostic marker in oral cancers, including all stages of OTSCC . In addition, stromal compounds, such as activin A, tenascin‐C, and fibronectin, have shown prognostic power in OTSCC .…”
Section: Discussionmentioning
confidence: 99%
“…Vascular endothelial growth factor and other growth factors such as epidermal growth factor are derived from stromal cells and endothelial cells, and promote tumour angiogenesis, which enhances tumour growth, survival, and metastasis . In OTSCC, CAFs identified by the use of α‐smooth muscle actin have been reported as key players in tumour progression, and they serve as an important prognostic marker in oral cancers, including all stages of OTSCC . In addition, stromal compounds, such as activin A, tenascin‐C, and fibronectin, have shown prognostic power in OTSCC .…”
Section: Discussionmentioning
confidence: 99%
“…Evidence has shown that the close communication between TME and cancer cells contributes to invasion and metastasis in tumors . As the key component of the TME, CAFs are important regulators of tumor growth, angiogenesis, invasion, metastasis, and poor prognosis in many malignancies . Recently, HSF1 expression in CAFs has attracted substantial attention regarding its role in tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, activated CAFs have been thought to be characterized by the expression of α‐SMA, FSP‐1, FAP, fibronectin and Vimentin . Of note, increased infiltration of CAFs in tumor stroma is correlated with poor prognosis in many malignancies, including breast cancer, colorectal cancer and oral cancer …”
Section: Introductionmentioning
confidence: 99%
“…Additionally, treatment and prognosis of HNSCC are proposed according to the TNM stage, but nevertheless it has been observed that patients with the same TNM receiving similar therapeutic approaches have different evolution, evidencing that TNM is not always effective and new prognostic markers (adjuvants for TNM) are imperative in HNSCC. The aggressive features of HNSCC are dependent on the interactions between neoplastic cells and tumour microenvironment components . Neoplastic cells are in permanent interaction with the microenvironment and cells of the connective tissue, such as cancer‐associated fibroblasts (CAF) and immune cells.…”
Section: Discussionmentioning
confidence: 99%